99mTc bone scintigraphy does not affect preoperative workup for patients with potentially resectable esophageal squamous cell carcinoma. Issue 16 (10th July 2022) - Wei, Xiu‐feng; Chen, Xian‐kai; Lu, Lu; Luo, Peng; Xu, Lei; Xie, Hou‐nai; Yang, Ya‐fan; Yu, Yong‐kui; Li, Hao‐miao; Liu, Qi; Zhang, Rui‐xiang; Qin, Jian‐jun; et al.
Abstract: Background: 99m Tc bone scintigraphy (BS) is the mainstay and most widely used technique in evaluation of bone metastasis (BM) in China. This study aimed to investigate the value of 99m Tc BS in preoperative workup for patients with potentially resectable (cT1−4a N0−3 ) esophageal squamous cell carcinoma (ESCC). Methods: This prospective cross‐section clinical trial (ChiCTR1800020304) enrolled a total of 385 patients with ESCC diagnosed at thoracic surgery clinic from October 2018 to September 2020. All patients were diagnosed with stage cT1−4a N0−3 and were potential candidates for surgical resection. BS was performed preoperatively and the treatment strategy was changed after confirmation of BM. The primary endpoint was the rate of change of the treatment regimen because of BM, while the secondary endpoint was the rate of positive BS findings. Results: Out of the 385 patients, only two (0.5%) changed their treatment regimen because of BM. The rate of positive BS findings was 1%, while two patients (0.5%) had false‐positive or false‐negative results. The BS diagnostic performance for BM was sensitivity 50%, specificity 99.5%, positive predictive value 50%, negative predictive value 99.5%, and accuracy 99.0%. There was no significant difference in BM in relation to age, sex, tumor location or clinical stage. Conclusion: Our data demonstrated that 99m Tc bone scintigraphy does not significantly affect the preoperative workup in patients with potentially resectable ESCC, especially in early clinical stage patients.